2023
DOI: 10.1038/s41467-023-37010-0
|View full text |Cite
|
Sign up to set email alerts
|

Non-falciparum malaria infection and IgG seroprevalence among children under 15 years in Nigeria, 2018

Abstract: Plasmodium falciparum (Pf) is the dominant malaria parasite in Nigeria though P. vivax (Pv), P. ovale (Po), and P. malariae (Pm) are also endemic. Blood samples (n = 31,234) were collected from children aged 0-14 years during a 2018 nationwide HIV survey and assayed for Plasmodium antigenemia, Plasmodium DNA, and IgG against Plasmodium MSP1-19 antigens. Of all children, 6.6% were estimated to have Pm infection and 1.4% Po infection with no Pv infections detected. The highest household wealth quintile was stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
(70 reference statements)
1
2
0
Order By: Relevance
“…IgG levels for these latter three targets remained low throughout the first 2 years of life, but high variability in AMA1 and PfMSP1 antigens as children aged showed P. falciparum exposure and adaptive immune responses to these immunogenic antigens. Maternal transfer of non-falciparum IgG was also noted in this neonatal study population (24) and showed similar temporal dynamics to the P. falciparum IgG targets. Similar trends of waning maternally-derived IgG levels have been found in previous studies, with antimalarial IgG levels decreasing to their lowest between 6-9 months of age in other high-transmission settings and the lowest proportion of seropositive infants was seen at approximately 10 months for AMA1 and PfMSP1 (30, 31).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…IgG levels for these latter three targets remained low throughout the first 2 years of life, but high variability in AMA1 and PfMSP1 antigens as children aged showed P. falciparum exposure and adaptive immune responses to these immunogenic antigens. Maternal transfer of non-falciparum IgG was also noted in this neonatal study population (24) and showed similar temporal dynamics to the P. falciparum IgG targets. Similar trends of waning maternally-derived IgG levels have been found in previous studies, with antimalarial IgG levels decreasing to their lowest between 6-9 months of age in other high-transmission settings and the lowest proportion of seropositive infants was seen at approximately 10 months for AMA1 and PfMSP1 (30, 31).…”
Section: Discussionsupporting
confidence: 70%
“…To dichotomize seropositivity to each antigen, a 2-component FMM of the log 10 -transformed MFI-bg signal was fit for each antigen’s IgG response ( 22 ), and the positivity cutoff was determined by the lognormal mean of the first component (presumed seronegative) plus three standard deviations ( 21 ). Due to high levels of P. falciparum exposure and seropositivity, a 6-component FMM was created for PfMSP1 and AMA1 to best define the first, putative seronegative, component ( 24 ). Due to the transition between passively-transferred IgG in child serum, and actively acquired serum antibodies through natural exposure, different seropositivity cutoffs were generated for the population of children under 2, and the population of children from 2 to 4 years of age.…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge this is the first time P. vivax is being identified in Ghana. However, several cases of P. vivax have been identified in various sites in Nigeria [29][30][31][32], Cameroon [33,34], Benin [35] and Senegal [36]. In this current study, the Pf/Pv/Pm mixed-infections were seen in two males (7 and 16 years), from two different but contiguous districts (Abura-Asebu-Kwamankese district and Cape Coast metropolis).…”
Section: Plos Global Public Healthmentioning
confidence: 49%
“…In the same vein, 38.4% of global malaria deaths occurred in Nigerian children younger than five years old in 2021 [1]. Further, P. vivax, P. ovale wallikeri, P. ovale curtisi and P. malariae are non-Plasmodium falciparum species incriminated in malaria disease [8][9][10].…”
Section: Introductionmentioning
confidence: 99%